A novel sustainable metal organic framework as the ultimate aqueous phase sensor for natural hazards: detection of nitrobenzene and F at the ppb level and rapid and selective adsorption of methylene blue - Shahid, M; Saleh, Hatem A. M; Qasem, Khalil M. A; Ahmad, Musheer (CrystEngComm, 2020)
Herein, a new cationic Cu( ii )-based porous and water stable metal-organic framework (MOF), [{Cu(bipy) 1.5 (H 2 pdm)}·2NO 3 ·H 2 O] n ( Cu-MOF-1 ), is synthesised via a slow evaporation process using pyridine-2,6-dimethanol (H 2 pdm) and 4,4′-bipyridine (bipy). The MOF is characterized using Fourier-transform infrared (FTIR) spectroscopy, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), magnetic analysis and single-crystal X-ray diffraction analysis. The structural unit of Cu-MOF-1 consists of two Cu( ii ) ions bridged by bipy and supported by H 2 pdm. This material exhibits excellent sensing ability for nitrobenzene (NB) and fluoride ions (F − ) in 100% aqueous medium with an ultra-low limit of detection of 0.093 and 1.203 ppb for NB and F − , respectively. The detection of nitro aromatic compounds (NACs) was found to be governed by photo-induced electron transfer (PET) and fluorescence resonance energy transfer (FRET) mechanisms, while vapour pressure played a major role in NB detection, with a high fluorescence quenching of 96.4%. Moreover, the MOF showed high water stability, significant recyclability and microporosity. The MOF was also employed for the adsorption and separation of methylene blue (MB) from a mixture of three dyes (MB, rhodamine-B and methyl orange). At equilibrium, the removal percentage of Cu-MOF-1 for MB was 98.23% and the mechanism of dye adsorption was also explored. Thus, the present MOF was determined to be a sustainable multifunctional material for the aqueous phase sensing of hazardous NB and fluoride ions, as well as an excellent dye adsorbent. A novel metal organic framework (MOF) exhibits good aqueous phase sensing properties towards nitrobenzene and fluoride anions and selective adsorption/separation ability for methylene blue.